Evaluation De La Prematurite Superieure Ou Egale A 32 Semaine D’amenorhée A L’hopital Regional De Ziguinchor Au Sud Du Senegal (Afrique De L’ouest) - Niokhor, Diouf Francois; Bintou, Diallo Fatima; Lamine, Thiam; Yaya, Kane; Demba, Ba Idrissa; Abouba, Ba; Mactar, Faye Pape; Ousmane, Ndiaye; Modou, Gueye; Ramatoulaye, Diagne Ndeye (European Scientific Journal, ESJ, 2017)
Introduction: Prematurity is one of the leading causes of neonatal death in Africa. The objective of this work was to assess the preterm birth at the pediatric service of the regional hospital of Ziguinchor. Material and methods: This was a prospective, descriptive and analytical study of the case of hospitalized newborns whose age was between 32 SA to 36SA + 6 days. The study was conducted from May 21, 2013 to May 21, 2014. We included all premature infants at age ≥ 32SA.Those presenting a malformation were not included. We studied maternal socio-demographic, obstetric and neonatal parameters. Results: We have identified 140 newborns out of a total of 342 Preterm births and 2292 maternity births, a prevalence of 40.9% compared to preterm infants and 6.10% in relation to all births. 51.4 percent of mothers came from urban areas, 63.5 percent were between 20 and 34 years of age, not attending school in 45.7 percent, married in 72.9 percent and without work in 94.3 percent. The average gestures represented 3.09 . Arterial hypertension was the most common medical condition (67.7%). The followup was done by a midwife (82.1%) and 23.5% had received at least 4 NPC. Eclampsia and pre-eclampsia (48.9%) and RPM (42.8%) were common obstetric pathologies. The delivery was by caesarian (51.4%), hospital (92.1%), cephalic presentation (80%), with an average weight of 1816.79 g. An RCIU (16.4%), an RPM (61.9%). At birth, a DR (16.4%) was noted due to MMH (43.7%) and transitory tachypnea (50%). Asphyxia was reported in 3.5%. During hospitalization (6.7 days on average), 6.4% had RD caused by infection (77.7%). Other complications were infection (64.4%), hypoglycemia (28.5%), digestive hemorrhage (7.01%). The fatality rate was 7.9% due to infection (63.3%), DR (18%), haemorrhage (9%). The anthropometric measurements at the exit: P 1887.9g, T: 38.3cm, PC: 30.9cm; at 1 month P: 2387.1g, T: 46.6cm, PC: 32.8cm; at 30 months P: 12.1kg, T: 89.5cm, PC: 48.4cm. Conclusion: Moderate preterm birth accounts for almost half of the cases of prematurity in our series. Their optimal management would go through a better obstetric-neonatal collaboration but above all by the installation of kangaroo mother units